Monobody adapter for functional antibody display on nanoparticles for adaptable targeted delivery applications - C. Albert; L. Bracaglia; A. Koide; J. DiRito; T. Lysyy; L. Harkins; C. Edwards; O. Richfield; J. Grundler; K. Zhou; E. Denbaum; G. Ketavarapu; et al. (Nature Communications, 2022)
Targeted nanoparticle delivery to sites of interest is important for targeted therapeutics. Here, the authors improve the targeting efficiency of antibodies on nanoparticles using a monobody adapter to correctly orientate the antibody to preserve targeting function and demonstrate application in targeting the vascular endothelium of human kidneys.